Structure and pro-toxic mechanism of the human Hsp90/PPIase/Tau complex. Issue 1 (December 2018) - Oroz, Javier; Chang, Bliss; Wysoczanski, Piotr; Lee, Chung-Tien; Pérez-Lara, Ángel; Chakraborty, Pijush; Hofele, Romina; Baker, Jeremy; Blair, Laura; Biernat, Jacek; Urlaub, Henning; Mandelkow, Eckhard; et al.
Abstract The molecular chaperone Hsp90 is critical for the maintenance of cellular homeostasis and represents a promising drug target. Despite increasing knowledge on the structure of Hsp90, the molecular basis of substrate recognition and pro-folding by Hsp90/co-chaperone complexes remains unknown. Here, we report the solution structures of human full-length Hsp90 in complex with the PPIase FKBP51, as well as the 280 kDa Hsp90/FKBP51 complex bound to the Alzheimer's disease-related protein Tau. We reveal that the FKBP51/Hsp90 complex, which synergizes to promote toxic Tau oligomers in vivo, is highly dynamic and stabilizes the extended conformation of the Hsp90 dimer resulting in decreased Hsp90 ATPase activity. Within the ternary Hsp90/FKBP51/Tau complex, Hsp90 serves as a scaffold that traps the PPIase and nucleates multiple conformations of Tau's proline-rich region next to the PPIase catalytic pocket in a phosphorylation-dependent manner. Our study defines a conceptual model for dynamic Hsp90/co-chaperone/client recognition. The chaperone Hsp90 plays a key role in maintaining cellular homeostasis. Here the authors provide structural insights into substrate recognition and the pro-folding mechanism of Hsp90/co-chaperone complexes by studying the complex of Hsp90 with its co-chaperone FKBP51 and the substrate Tau bound Hsp90/FKBP51 ternary complex using a NMR based integrative approach.